Cardiovascular outcomes of patients treated for non-Hodgkin lymphoma with first-line doxorubicin-based chemotherapy. Issue 14 (6th December 2022) - Zduniak, Alexandra; Lévêque, Emilie; Perdrix, Anne; Etancelin, Pascaline; Ménard, Anne-Lise; Lenain, Pascal; Contentin, Nathalie; Pépin, Louis-Ferdinand; Leprêtre, Stéphane; Lemasle, Emilie; Lanic, Hélène; Stamatoullas-Bastard, Aspasia; et al.
Abstract: We conducted a single-center retrospective study to assess cardiovascular (CV) toxicity and treatment discontinuation for CV toxicity in diffuse large B-cell lymphoma (DLBCL) or follicular lymphoma (FL) patients treated with immunochemotherapy (R-CHOP-like). Between 2006 and 2017, 433 patients were included (DLBCL: n  = 345, FL: n  = 88). The median age was 63 years (50–73). We defined three types of CV toxicity: early-onset cardiovascular toxicity (the event occurred within 6 months following treatment start); subacute toxicity (the event occurred between 6 months and 1 year after treatment start) and late toxicity (the event occurred 1 year or more after treatment start). Forty-eight (11.1%) patients experienced at least one anthracycline-related CV event. Seven patients experienced treatment discontinuation due to CV toxicity. Early-onset and subacute cardiac events were primarily acute heart failure (34.3%) and atrial fibrillation (28.6%). History of ischemic heart disease ( p  = 0.02) and valvular heart disease ( p  = 0.03) were associated with a higher risk of anthracycline-related CV event occurrence.